Haptic feedback for multilayer cutting - Rianto, Sugeng; Li, Ling; Hartley, Bruce (IOS Press, 2008)
An approach in effectively estimating the force feedback for a tactile haptic based on multi-proxy rendering for 3D surface cuttings for a virtual surgery simulation is described in this paper. The force-models representing haptic force-feedback are approximated using D'Alembert's principle in the mechanic case of spring-damper-stiffness interaction of the surfaces. We also propose a combination between mesh refinement and adaptive re-meshing to create a progressive cutting over the layering surfaces. Experimental results prove that the physical interaction to create cutting paths over the multilayer surfaces can be deliver smoothly with haptic in real time with 3D visual stereo on a PC.